Problematika Pembelajaran Tahfizh Qur'an - Agustia Fatma Rini; Al Ikhlas (Prodi Pendidikan Keagamaan Islam, 2022)
Tahfizh Qur’an is the process of memorizing the Qur'an in order to maintain its mulishness and authenticity. This study aims to find out the problems of learning the tahfizh Qur’an and efforts in overcoming them. This research uses a descriptive qualitative approach. The data collection techniques are observation, interviews, and documentation. Interviews are conducted with the principal, tahfizh teachers, and students. Then the collected data were analyzed by qualitative data analysis techniques. From the results of this study, it was found that: 1) The problems of learning tahfizh Qur’an in junior high schools UNP laboratory development are motivated by three factors, namely factors from students, factors from educators, and factors from schools. 2) The efforts made by the school to solve the problem of tahfizh learning are to provide special guidance, provide motivation to students, restrain students in class, group students based on their abilities, and increase class hours.